Latino and Latina Adolescents' Help‐seeking Behaviors and Attitudes Regarding Suicide Compared to Peers with Recent Suicidal Ideation. Issue 5 (12th January 2015) - De Luca, Susan; Schmeelk‐Cone, Karen; Wyman, Peter
<x xml:space="preserve">Abstract</x> Although Latinas have consistently reported higher rates of suicidal behavior for the past 20 years (CDC, 1996), there is a dearth of information regarding their help‐seeking attitudes and behaviors when dealing with distress and suicide. Associations between adolescents' ideation and help‐seeking from adults were different for non‐Hispanic Whites and Latinos from 14 high schools (N = 4, 983). Among females, ideators and Latinas reported lower levels of help‐seeking attitudes than nonideators and non‐Hispanic Whites. Males showed interaction effects of ideation by race/ethnicity on help‐seeking. Within sex by race/ethnicity, differences showed that while non‐Hispanic White students reported consistent differences between suicidal ideation and no reported suicidal ideation, Latinos were more similar between these groups, particularly with having support from friends and family to seek help from adults. Research should clarify how culture contributes to decreased help‐seeking norms among those with suicidal ideation.